Automation System of Gallon Filling Valve Based on Outseal PLC and Haiwell Interface - Fitriyanto, Indra; Aziz, Rofan; Fatwasauri, Icha; Kurnianingtyas, Rahajeng; Pebriari, Rizky Budiman (Emitor: Jurnal Teknik Elektro, 2025)
Water is one of the basic needs that must be met by humans. To meet drinking needs in urban areas, the easiest and cheapest way for people is to buy refilled drinking water. However, the process of filling drinking water is still done manually by humans, so it is prone to errors. Therefore, in this study, the automation of gallon water filling will be carried out using Outseal PLC. Outseal PLC is used because of its relatively low price and greater reliability when compared to a microcontroller. In addition, the gallon filling status will also be displayed on the HMI display. In this study, a trial will be conducted on a drinking water installation at the Indramayu State Polytechnic (Polindra). Before testing, the flow sensor used must be calibrated first. Calibration is done by comparing the results of the flow sensor readings with the PDAM water meter to obtain a conversion of pulses to liters of water. Based on the tests that have been carried out, the results obtained are that the system can work well, namely the valve and pump turn on when the start button is pressed and will automatically turn off when the sensor has read a water volume of 19 liters. However, the sensor shows different readings when the water source used has a different water flow rate. In the first calibration using PDAM water flow rate, a pulse value of 464 was obtained for 1 liter of water, while in the second calibration using pump water flow rate, a pulse value of 566 was obtained for 1 liter of water. This is caused by the sensor used having less sensitivity to changes in water flow rate, which results in different reading results for different water flow rate. Therefore, the sensor must be recalibrated if it is to be used in water installations with different water flow rate. Although the sensor reading values are inconsistent, from tests carried out 40 times, the difference in readings is less than 10%.